The Toxicity, Pathophysiology, and Treatment of Acute Hydrazine Propellant Exposure: A Systematic Review. Issue 3 (26th February 2021) - Nguyen, HoanVu N; Chenoweth, James A; Bebarta, Vikhyat S; Albertson, Timothy E; Nowadly, Craig D
ABSTRACT: Introduction: Hydrazines are highly toxic inorganic liquids that are used as propellants in military and aviation industries, such as the U.S. Air Force F-16 Emergency Power Unit and SpaceX SuperDraco Rockets. The most commonly used derivatives include hydrazine, monomethylhydrazine, and 1, 1-dimethylhydrazine (unsymmetrical dimethylhydrazine). Industrial workers in close contact with hydrazines during routine maintenance tasks can be exposed to levels well above the National Institute for Occupational Safety and Health relative exposure limits. Materials and Methods: A systematic review was performed using PubMed, Web of Science, Google Scholar, National Aeronautics and Space Administration Technical Server, and Defense Technical Information Center, and data related to hydrazine exposures were searched from inception to April 2020. Publications or reports addressing hydrazine toxicity, pathophysiology, and treatment of hydrazine fuel exposure were selected. Results: Acute toxic exposures to hydrazine and its derivatives are rare. There are few case reports of acute toxic exposure in humans, and data are largely based on animal studies. The initial search identified 741 articles, manuscripts, and government reports. After screening for eligibility, 51 were included in this review. Eight articles reported acute exposures to hydrazine propellant in humans, and an additional 14 articles reported relevant animal data. Conclusions: Exposure to small amounts of hydrazine and its derivatives can cause significant soft tissue injury, pulmonary injury, seizures, coma, and death. Neurologic presentations can vary based on exposure compound and dose. Decontamination is critical as treatment is mainly supportive. High-dose intravenous pyridoxine has been suggested as treatment for hydrazine-related neurologic toxicity, but this recommendation is based on limited human data. Despite recent research efforts to generate less toxic alternatives to hydrazine fuel, it will likely continue to have a role in military and aviation industries. Aerospace and military physicians should be aware of the toxicity associated with hydrazine exposure and be prepared to treat hydrazine toxicity in at-risk populations.